2021
DOI: 10.4143/crt.2020.1010
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Acute Kidney Injury in Lung Cancer Patients

Abstract: Acute kidney injury (AKI) in cancer patients is associated with increased morbidity and mortality. The incidence of AKI in lung cancer seems to be relatively higher compared with other solid organ malignancies, although its impact on patient outcomes remains unclear. Materials and MethodsThe patients newly diagnosed with lung cancer from 2004 to 2013 were enrolled in this retrospective cohort study. The patients were categorized according to the presence and severity of AKI. We compared all-cause mortality and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Notably, acute kidney failure was presented among the top 10 factors for lung cancer only. Previous studies have reported the incidence of acute kidney injury is higher in lung cancer patients than in other malignancies 35 , and it is believed that acute kidney injury can negatively affect lung physiology by altering fluid balance, acid-base balance, and vascular tone 36 . The presence of albuminuria has been found to be associated with the incidence of lung cancer in large-size observational studies 37 , 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, acute kidney failure was presented among the top 10 factors for lung cancer only. Previous studies have reported the incidence of acute kidney injury is higher in lung cancer patients than in other malignancies 35 , and it is believed that acute kidney injury can negatively affect lung physiology by altering fluid balance, acid-base balance, and vascular tone 36 . The presence of albuminuria has been found to be associated with the incidence of lung cancer in large-size observational studies 37 , 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were consistent with previous studies that RDW/ALB was associated with all-cause mortality of ICU patients with AKI, with a higher ratio indicating a higher risk of mortality. Existing studies showed that AKI stages were independently associated with the mortality of ICU patients ( 42 , 43 ). In our study, we found moderate and high RDW/ALB ratios increased the risk of all-cause mortality in each AKI stage.…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury (AKI) is a frequent complication of either the underlying malignancy or its treatment and is an independent predictor of mortality in patients with cancer[ 20 , 21 ]. The incidence of AKI in a large Danish cohort of cancer patients was reported to be 17.5% at 1 year and 27% over the course of 5 years, which highlights the enormity of the problem[ 22 ].…”
Section: Clinical Scenario 1: Acute Kidney Injury In Cancermentioning
confidence: 99%